ATP redirects cytokine trafficking and promotes novel membrane TNF signaling via microvesicles. Issue 5 (18th February 2019) - Soni, Sanooj; O'Dea, Kieran P.; Tan, Ying Ying; Cho, Kahori; Abe, Eiko; Romano, Rosalba; Cui, Jiang; Ma, Daqing; Sarathchandra, Padmini; Wilson, Michael R.; Takata, Masao
ABSTRACT: Cellular stress or injury induces release of endogenous danger signals such as ATP, which plays a central role in activating immune cells. ATP is essential for the release of nonclassically secreted cytokines such as IL‐1β but, paradoxically, has been reported to inhibit the release of classically secreted cytokines such as TNF. Here, we reveal that ATP does switch off soluble TNF (17 kDa) release from LPS‐treated macrophages, but rather than inhibiting the entire TNF secretion, ATP packages membrane TNF (26 kDa) within microvesicles (MVs). Secretion of membrane TNF within MVs bypasses the conventional endoplasmic reticulum– and Golgi transport–dependent pathway and is mediated by acid sphingomyelinase. These membrane TNF–carrying MVs are biologically more potent than soluble TNF in vivo, producing significant lung inflammation in mice. Thus, ATP critically alters TNF trafficking and secretion from macrophages, inducing novel unconventional membrane TNF signaling via MVs without direct cell‐to‐cell contact. These data have crucial implications for this key cytokine, particularly when therapeutically targeting TNF in acute inflammatory diseases.—Soni, S., O'Dea, K. P., Tan, Y. Y., Cho, K., Abe, E., Romano, R., Cui, J., Ma, D., Sarathchandra, P., Wilson, M. R., Takata, M. ATP redirects cytokine trafficking and promotes novel membrane TNF signaling via microvesicles. FASEB J. 33, 6442–6455 (2019). www.fasebj.org